Enhancing Students' Learning Outcomes and Science Process Skills through STEM Project-Based Learning on Global Warming Topics - Hafitri, Mona Lisa; Efwinda, Shelly (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
Global warming is a major concern, and tackling it via education is crucial. The purpose of this study is to investigate the impact of combining the Science, Technology, Engineering, and Mathematics (STEM) approach with the Project-based Learning (PjBL) model on students' learning outcomes and science process skills in global warming topics. The study, which used a one-group pretest-posttest design, collected data from 33 grade XI students via essay questions and observation sheets to assess learning outcomes and science process skills. Critical indicators of science process abilities were observing, classifying, interpreting, predicting, applying concepts, communicating, and forming conclusions. Students worked on a STEM-based project to build a flood-resistant house over the course of five meetings (including the pretest and post-test). The findings revealed considerable improvements: learning outcomes increased by 0.6 (medium category), while science process skills improved by 0.7 (high category). Observations revealed that pupils' scientific process skills were excellent. The Wilcoxon test revealed a significant difference between students' learning outcomes and science process abilities before and after the intervention, with a Sig (2-tailed) value of 0.000. The study indicated that combining the STEM method with the PjBL model improves students' learning outcomes and scientific process abilities. However, the small sample size implies that the results may not be generalizable. The consequence is that integrating the STEM method and the PjBL model provides an innovative option in physics education, improving learning outcomes and scientific process skills.